Saying "no" to being uprooted: The impact of family and gender on willingness to relocate - Baldridge,David; Eddleston,K. A.; Veiga,J. F. (Journal of Occupational and Organizational Psychology, 2006)
Although career research contends that women managers and professionals are less willing than men to relocate, much of the previous research has been either limited by comparative sampling issues, or has not fully accounted for the role of family. To address these issues we gathered survey data from managers and professionals in 102 large companies by identifying pairs of individuals from each firm who worked in the same division, location, and functional area, who were similar in age (± 5 years), yet differed in gender ” resulting in a comparatively matched sample of 333 male and 333 female respondents. To account for the role of family, we tested a model that first controlled for the impact of previous determinants of willingness to relocate, and then examined the impact of four family attributes including spouse's contribution to family income, presence of preschool-aged children at home, and the perceived strength of spouse's and children's community ties. We also examined the moderating role of gender in explaining the impact of these attributes. Results indicate that the inclusion of family attributes increased the amount of variance explained in our regression model. Moreover, beyond substantiating a significant main effect for gender ” that is, women managers are less willing to relocate ” we also found that gender interacts with family attributes to further dampen a woman's willingness to relocate.
Keywords: Management